Loan Recovery and Asset Quality of Commercial Banks: An Empirical Analysis - Ahmed, Jaynal Uddin (Indian Journal of Finance, 2010)
The recovery performance of commercial banks is the sin qua non for their liquidity of funds. Loan recovery is the main the factor which determines the quality of loan assets of banks. The mounting overdues lead to high level of non performing assets (NPA) and thereby deteriorate the asset quality. It consequently restricts the banks’ lending capacity and stands in the way of dilution of funds to developmental activities and hence, the socio economic development of the area gets impacted. Thus, improving the quality of loan assets is the true test of improved efficiency of the banking system.